Trichobezoar presenting as an acute abdominal obstruction in a 17-year-old girl. (3rd April 2022) - Bayramoglu, Zuhal; Comert, Rana Gunoz; Erginel, Basak; Baziki, Abdulkadir
ABSTRACT: Trichobezoars are hairballs that combine with food residue in the digestive tract as a result of ingesting hair. A 17-year-old girl was admitted to the emergency department with abdominal pain and vomiting for 3 days. She had been having digestive difficulty and bloating for the previous 2 months. An abdominal radiograph demonstrated air-fluid levels consistent with ileus, and an ultrasound showed hyperechoic material in the stomach and ileum. Computed tomography demonstrated images of trapped air which was considered diagnostic of a bezoar. At laparotomy, a large mass was removed from the stomach. As the bezoar extended through the pylorus and duodenum and there were mobile masses palpable in the ileum, it required a second incision to remove them. For some years she had had a habit of swallowing hair which she found on her pillow and there was a history of an obsessive personality trait and hyperactivity for which she agreed to attend a psychiatric clinic. Abbreviations: BMI: body mass index; CT: computed tomography; Hb: haemoglobin; IV: intravenous; WHO: World Health Organization